INNOVATIVE BEHAVIOR AND EMPLOYEE JOB SATISFACTION IN TELECOMMUNICATIONS SECTOR - Anes Hrnjić; Amila Pilav-Velić; Irma Đidelija; Hatidža Jahić (Economic Review)
The prevailing characteristic of the current business market is accelerated dynamics and remarkable change power, which require continuous adjustment of strategy. Employees are crucial drivers for optimal handling and implementing changes and innovations. The telecommunications sector is a major segment of the services industry and companies´  organizational behavior in terms of innovation is determined by various factors whose number, direction and intensity are not yet clearly defined. The research is aimed to investigate the influence of job satisfaction oninnovative capacity development of telecom operators by examining effectiveness of HRM practices in the innovation process. The methodology consists of suitable instruments for assessment of employee satisfaction and innovative behavior. The data was analyzed using linear regression. The results showed that job satisfaction expressed through compliance of challenging tasks, management practices, working conditions, corporate culture, compensation system, and professional competence significantly increases employees´  innovative behavior in the process of creating novel methods, techniques and instruments of labor or finding original solutions for on-going issues and changes in the business environment. The calculated values of the coefficients within the constructed models confirm the research hypothesis, which states that job satisfaction has a positive influence on innovative behavior of employees and improvement in work tasks.